The protection of the “artificial” origin of plants and food: between paradoxes and new meanings (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The essay aims to investigate concerns about food origin with a keen eye to biotechnological products. The research covers two specific cases: the recent Proposal for a Regulation on plants obtained by new genomic techniques; and National legislative initiatives on cultivated cell-based food, with specific regard to the Italian experience. Both cases will underline the interconnection between food origin protection and consumer attitudes towards new techniques. The paper also proposes reviewing policies on biotech food products to support sustainable models and to guide consumers towards aware consumption.
Keywords: Origin; Sustainability; New genomic techniques; European Law; law and scientific culture; consumers attitudes